2017
DOI: 10.1161/circresaha.117.311327
|View full text |Cite
|
Sign up to set email alerts
|

MerTK Cleavage on Resident Cardiac Macrophages Compromises Repair After Myocardial Ischemia Reperfusion Injury

Abstract: Rationale: Clinical benefits of reperfusion after myocardial infarction are offset by maladaptive innate immune cell function, and therapeutic interventions are lacking. Objective : We sought to test the significance of phagocytic clearance by resident and recruited phagocytes after myocardial ischemia reperfusion. Methods and Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
173
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(181 citation statements)
references
References 43 publications
8
173
0
Order By: Relevance
“…MerTK cleavage promotes necrotic core formation in advanced atherosclerosis and cardiac tissue injury in myocardial infarction. 9,31 With regard to atherosclerosis, Cai et al found that MerTK signaling stimulated the synthesis of SPMs over LTs both in isolated murine and human macrophages as well F I G U R E 5 RvD1 restores CM-induced defects in efferocytosis and MerTK cleavage. A, Macrophages were treated with Veh or 10 nM RvD1 for 20 minutes prior to the addition of conditioned media (CM) from senescent cells.…”
Section: Discussionmentioning
confidence: 99%
“…MerTK cleavage promotes necrotic core formation in advanced atherosclerosis and cardiac tissue injury in myocardial infarction. 9,31 With regard to atherosclerosis, Cai et al found that MerTK signaling stimulated the synthesis of SPMs over LTs both in isolated murine and human macrophages as well F I G U R E 5 RvD1 restores CM-induced defects in efferocytosis and MerTK cleavage. A, Macrophages were treated with Veh or 10 nM RvD1 for 20 minutes prior to the addition of conditioned media (CM) from senescent cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, restoration of the blood flow can induce even worse microstructural destruction, termed myocardial ischemia/reperfusion injury (MIRI), which lessens the beneficial effect of reperfusion therapy [1]. Recently, a series of in vitro and in vivo studies have demonstrated that innate inflammation, apoptosis, autophagy, platelet activation, and oxidative stress contribute to MIRI [2][3][4][5][6]. However, there is no effective strategy for limiting or preventing MIRI, so a new molecular therapeutic target is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…80 these experiments indicate that cTM can incorporate large amounts of cardiomyocyte-derived material in vivo, even in the unperturbed hearts. 8 In this settings, a cTM subset expressing low levels of the major histocompatibility complex II (MHCII lo ) was phagocytically more active than other subsets both in vitro and in vivo. 8,20 This result is striking given the low renewal rate of adult cardiomyocytes, 81 and the lack of cardiomyocyte precursors.…”
Section: Phagocytosis and Pathologymentioning
confidence: 99%
“…8 In this settings, a cTM subset expressing low levels of the major histocompatibility complex II (MHCII lo ) was phagocytically more active than other subsets both in vitro and in vivo. 8,20 This result is striking given the low renewal rate of adult cardiomyocytes, 81 and the lack of cardiomyocyte precursors. It will be interesting to assess if this transfer of material from the cardiomyocyte is caused by a "trimming" process similar to synaptic pruning mediated by microglia in the brain, 3 and to define the possible mediators of this type of phagocytosis in the heart.…”
Section: Phagocytosis and Pathologymentioning
confidence: 99%
See 1 more Smart Citation